2001
DOI: 10.1080/02626660109492797
|View full text |Cite
|
Sign up to set email alerts
|

Regional hydrological research perspectives in the Niger Delta

Abstract: The Niger Delta at the southernmost part of Nigeria, is a large and ecologically sensitive region. Natural and anthropogenic activities, such as subsidence, sea-level rise, upstream dams and reservoirs, dredging and overabstraction of groundwater, disturb this equilibrium, leading to adjustments in ecological conditions and boundaries. Ecological changes affecting large areas cannot be explained by local observation. Relating observed effects to causes of environmental behaviour therefore requires a regionaliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
52
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 3 publications
0
52
0
Order By: Relevance
“…The Niger Delta environment Geologically, the Niger Delta is regarded as a modern delta (under 100 million years old in the Mesozoic era, Cretaceous period) (Galloway 1975;Okonny 2002). According to Short and Staeuble (1967) beyond into the Gulf of Guinea, resulted in the formation of this complex and fragile delta with a rich biodiversity (Abam 2001). The Niger Delta is regarded as the third largest wetland in the world (Uluocha and Okeke 2004;Umoh 2008), and the largest river delta and mangrove ecosystem with the greatest extension of freshwater swamps in Africa (Ajonina et al 2008;Dupont et al 2000;Ogon 2006).…”
Section: Geography and Peoplementioning
confidence: 99%
“…The Niger Delta environment Geologically, the Niger Delta is regarded as a modern delta (under 100 million years old in the Mesozoic era, Cretaceous period) (Galloway 1975;Okonny 2002). According to Short and Staeuble (1967) beyond into the Gulf of Guinea, resulted in the formation of this complex and fragile delta with a rich biodiversity (Abam 2001). The Niger Delta is regarded as the third largest wetland in the world (Uluocha and Okeke 2004;Umoh 2008), and the largest river delta and mangrove ecosystem with the greatest extension of freshwater swamps in Africa (Ajonina et al 2008;Dupont et al 2000;Ogon 2006).…”
Section: Geography and Peoplementioning
confidence: 99%
“…The effects may be localized but can be dramatic, e.g. : i) Yangtze: C A =28 mm/y before controls on groundwater withdrawal came into effect circa 1965 (18), ii) Mississippi near New Orleans: C A =5 to 25 mm/y (19), when organic soils are drained and oxidized (20), and gas is mined (21), iii) Niger: C A =25 to 125 mm/y from petroleum mining (22), iv) Chao Phraya: C A =50 to 150 mm/y from groundwater withdrawal (23), and v) Po: C A =60 mm/y during the peak of methane mining (24). The Po Delta has subsided 3.7 m in the 20 th Century, of which 81% is attributed to methane mining.…”
Section: Introductionmentioning
confidence: 99%
“…Water pollution in one part of the delta can readily be felt in other part. Studies conducted by Abam (2001), Oteri (1989Oteri ( , 2003 and Okagbue (2007) have identified salinity or saline water intrusion into groundwater aquifers and elevated levels of nitrates, ammonia and chlorides as major problems in the Niger Delta sub-region. Delta State one of the contiguous States with Bayelsa State in the Niger Delta for example, has problems of elevated levels of magnesium (Mg), Calcium (Ca), Bicarbonate (HCO 3 ) and hydrogen ion concentration.…”
Section: Introductionmentioning
confidence: 99%